Sybil exposed : the extraordinary story behind the famous multiple personality case - Nathan, Debbie (New York : Free Press, 2012)
Sybil: a name that resonates with legions of obsessed fans who followed the nonfiction blockbuster from 1973. The book rocketed multiple personality disorder into public consciousness and played a major role in having the diagnosis added to the psychiatric bible Diagnostic and Statistical Manual of Mental Disorders. But what do we really know about how Sybil came to be? The author provides evidence that the allegedly true story outlined in the mega-bestseller was largely fabricated. The actual identity of Sybil (Shirley Mason) has been available for some years, as has the idea that the book might have been exaggerated. But the author reveals the trio of women behind the legend: the willing patient, her ambitious shrink, and the imaginative journalist who spun their story into bestseller gold. This book draws from an enormous trail of papers, records, photos, and tapes to unearth the lives and passions of these three women whose story exploded into an epic movement with consequences beyond their wildest dreams.
Shirley -- Connie -- Flora -- Dr. Wilbur -- Miss Mason -- Professor Schreiber -- Manhattan -- The couch -- Addiction -- Clinical tales -- Convalescence -- Cure -- Impatience -- The edit -- The book -- The film -- Commitment -- Exposure -- Breakdown -- Contagion -- Containment -- Demise.
Includes bibliographical references (pages 247-282) and index.
Keywords: Sybil, -- 1923-1998 -- Mental health; Schreiber, Flora Rheta; Wilbur, C. B; Multiple personality -- Patients -- Biography; Hoaxes; Schreiber, Flora Rheta; Sybil, -- 1923-1998.; Wilbur, C. B; Hoaxes; Mental health; Multiple personality -- Patients; Biography